Magneto-active elastic shells with tunable buckling strength - Dong Yan (Nature Portfolio, 2021)
Predicting and controlling the (in)stability of thin shells are important tasks in many practical applications but hampered by the presence of imperfections. Here Yan et al. show that when the material composition is magnetic the conditions for collapse can simply be readjusted with external fields.